LPA Brief no. 11. Livestock production, consumption and trade: Key indicators - Mengesha, Y.; Ehui, Simeon K.; Jabbar, M.A.; Shapiro, Barry I. (International Livestock Research Institute, 1998)
Livestock production is a major contributor to economic development, both driving economic growth and benefiting from it. As an engine of growth, it provides increased income, employment, food and foreign exchange earnings, as well as better nutrition. As income increases with economic development, the share of animal products in the total food budget increases faster than that of cereals. This occurs because of the relatively high income elasticity of demand for animal products. This fact sheet gives some key indicators for 1993 derived principally from FAO (Food and Agriculture Organization of the United Nations) AGROSTAT data tapes. The data provide, at a glance, insight into the role of animal agriculture in developing countries. It highlights the production, consumption, import and export of the two major ruminant products, meat and milk. There may be discrepancies between FAO and other sources of data due to differences in pricing, aggregation and conversion factors used. For example, based on USDA (United States Department of Agriculture) data, the share of livestock in agricultural output for Ethiopia is about 40 %, but based on the FAO data it is about 27 %. The countries and the sub-regions selected in this fact sheet reflect the current mandate of the International Livestock Research Institute (ILRI). Consequently, only regional figures for the developed countries have been included to facilitate comparisons and highlight the potential for and consequences of livestock development. The country grouping in this fact sheet generally follows that of FAO, but further groupings by subregions have been provided to obtain better comparison across regions. Countries have been grouped by subregions based on their geographical proximity and level of economic development. For example, North Africa has been reported separately instead of under West Asia and North Africa (WANA); Sudan has been grouped in East Africa instead of North Africa; and Mexico has been grouped as part of Central America and the Caribbean instead of under North America.